PROTECTION OF WAR REPORTERS IN ARMED CONFLICT AREAS BASED ON INTERNATIONAL LAW (CASE STUDY OF THE IRAQ AND SYRIA CONFLICT) - Desia Rakhma Banjarani; Sri Sulastuti; Kisti Artiasha (Universitas Lampung, 2019)
The work of journalists in conflict zones to convey the facts of war objectively is often life-threatening. In several international treaties, provisions regarding the protection of journalists working in conflict areas have been included, but there are some obstacles to enforcing the provisions of these international agreements. The issue to be discussed in this research is how is the protection of journalists in armed conflict based on international treaties in humanitarian law? And what about criminal liability for offenders who violate humanitarian law (war) by